Om Regine Normanns biografi med påfølgende debatt: Slik biografen ser det - Willumsen, Liv Helene (Nordlit, 1998)
I Nordlit 2 (1997) har Ragnhild Engelskjøn et innlegg med tittelen «Debatten rundt Liv H. Willumsens biografi Havmannens datter: Regine Normann—et livsløp», der hun drøfter en debatt som oppsto i avisen Nordlys etter utgivelsen av Regine Normanns biografi høsten 1997. (…) Med utgangspunkt i egen lesing av biografien forsøker Engelskjøn å klargjøre en del posisjoner knyttet til biografiskriving, og hun oppfordrer til fortsatt diskusjon om emnet. Som forfatter av Regine-Normann-biografien vil jeg gjerne få komme med noen betraktninger i forlengelsen av Engelskjøns innlegg. This essay is written as part of a debate related to the biography as genre, following the publishing of my biography Havmannens datter. Regine Normann - et livsløp [The merman's daughter. Regine Normann - a life story] (1997). On one hand the essay contains arguments related to this specific biography. On the other hand, it contains general points of view related to biography as genre. The author defines biography as a written life-story about a person different from the biographer himself or herself. A biography is a work according to historical methods, as it is based on historical sources and has an explicit claim to documentation inherent. In the specific biography on Regine Normann, which is styled as a story, strict demands to historical references are practiced. Still the biography in its final form is dependant upon interpretation of the sources.As more general points on biography as genre the essay argues that competence within documentation is of uttermost importance for the work, as reliable historical sources are the fundament of any valid biography. The work of reference is emphasized, as the reader should have the possibility to control the factual information given. There is a demand that correct and accurate when referring to sources, and not inventing or adding information which can not be documented.It is further argued for a division line between biography writing and literary analysis, in cases wherein the biography is written on an author. For that reason, literary analysis of fictional works does not have any place in a biography, but should be published as literary research.The interpretative function of the biographer is underlined, even in a text based on historical information. In a text formed along narrative lines, as is the case with Regine Normann's life story, the narrator has the authority and power to interpret documents and formulate the text in his own manner and according to his interpretation.  N.B: This article was originaly printed among the reviews of Nordlit nr. 3 and can also be found there, in its chronological place. It has been elevated by request of the author.